Rapid HPTLC based method for quality control: Simultaneous chemical analysis and antioxidant activity determination in herbal, nutraceutical and functional foods (2011)
ABSTRACT: Antioxidants belong to one of the most important group of compounds presented in herbs, nutraceuticals and damage. Hence, antioxidants have a high demanding and also their natural sources. A new procedure has been used to separate and quantify the free radical-scavenging activity of individual compounds from 44 samples of Calendula officinalis, 18 samples of Thymus vulgaris and 12 samples of Rosmarinus officinalis, based on the combination of HPTLC with a diode array detector (DAD) and postchromatographic DPPHƔ radical derivatization.